The Influence of Marketing Content to Motivate Tourists in Visiting The Lembar Selatan Area, West Lombok - Mulyawan, Firman Bramandhyta; An, Mu De; Idrus, Syech (Centre for Tourism Studies and Journal Publication of Sekolah Tinggi Pariwisata Mataram, 2025)
This study aimed to explore the key determinants shaping tourists' motivation to visit the Lembar Selatan Ecotourism site, with a particular focus on the role of informative content. Through a survey research design involving questionnaire distribution and documentation analysis, we sought to unravel whether informative content exerts a discernible influence on tourists' motivation to choose this ecotourism destination. Employing a simple linear regression analysis, we found that attitudinal factors, such as consumer perceptions and brand attitudes, played a more substantial role in shaping tourists' motivation compared to social predictors. Importantly, the results of our regression analysis demonstrated a significant relationship between informative content and the enhancement of tourists' motivation levels when visiting Ecotourism Lembar Selatan in West Lombok Regency. This underscores the pivotal role of marketing content in driving tourists' motivation